Implementation of the Waterfall Method in the Lalungguh Ecoprint Website - Dini Nurul Azizah; Raisa Mutia Thahir; Luthfi Dika Chandra; Muhammad Naufal Ardhani; Aditya Wicaksono; Gema Parasti Mindara (Universitas Islam Kuantan Singingi, 2025)
The rapid development of the digital era has encouraged MSME (Micro, Small, and Medium Enterprises) owners to adopt technology to enhance business efficiency and effectiveness. Lalungguh Ecoprint, an MSME engaged in sustainable fashion through the use of natural-based ecoprint techniques, still encountered obstacles in product promotion and manual financial record-keeping. This study aimed to develop a website that integrates product catalog management with financial recording into a unified, more efficient system. The development process employed the Waterfall method to ensure a structured and systematic workflow. Laravel was chosen as the primary framework due to its support for the Model-View-Controller (MVC) architecture, which simplifies code organization and modular feature development. MySQL was utilized as the database management system for its reliability in managing complex data storage. The resulting website enables real-time, centralized management of product and financial data and is accessible across multiple devices. This system is expected to enhance operational efficiency, streamline business activities, and broaden Lalungguh Ecoprint’s marketing reach through a digital platform.